Efficiently Detecting Metallodrug–Protein Adducts: Ion Trap versus Time‐of‐Flight Mass Analyzers. Issue 7 (18th March 2014) - Meier, Samuel M.; Babak, Maria V.; Keppler, Bernhard K.; Hartinger, Christian G.
Abstract Modern mass spectrometry techniques have increasingly found use in studies on the binding of anticancer metallodrugs to potential cellular targets. In this context, investigations on the detection efficiency of adduct formation between antiproliferative Ru(arene) complexes and proteins in dependence of the mass analyzer used in the electrospray ionization (ESI) mass spectrometer are presented. The potential in detecting adducts between the metal center and the protein was found to be dependent on the mass analyzer and the denticity of the metal–protein interaction. This might be related to the design of the mass analyzers with different conditions in the ion travelling pathways, which affects adducts when the protein acts as a monodentate ligand more highly than in cases when the protein is a multidentate ligand. This could also impact the biological activity and indicate different pathways of metabolism of biomolecule adducts.